Pelatihan Pembuatan Fermentasi Pakan Ternak Sebagai Upaya Pemenuhan Kebutuhan Pakan Pada Musim Kemarau Di Desa Buwun Mas, Kecamatan Sekotong, Lombok Barat - Arifin, Bustanul; Wahyu Agung Sakti, Lalu; Nursaid Rizalullael, Muh.; Istikomah, Istikomah; Hendrawan, Hendrawan; Hariyanto, Andi; Salasa, Danie; Ragil Qiansantang, Lalu; Azwan, Ahmad; Noviana, Tia; Suhardin, Suhardin; Yudiana, Pina (PT. ALHAFI BERKAH INDONESIA, 2024)
Abstract: Animal husbandry is an activity to fulfill needs within a period of 1-5 years for the people of Buwun Mas Village, Sekotong District, West Lombok Regency, population of 14,869 people. Difficulty in getting quality feed during the dry season is a problem that is still an obstacle to the healthy growth and development of livestock. Apart from the scarce availability of feed, the quality and nutrition contained in animal feed is inadequate. So it is very important to provide alternative training solutions for making fermented animal feed for breeders in Buwun Mas hamlet. The methods used to conduct training are observation and interviews with residents, to identify problems experienced by breeders. Meanwhile, the training implementation technique consists of several sessions, first; socialization of making fermented animal feed, second; discussion, and third; animal feed manufacturing practices. The conclusion from this service process is: Training in making fermented animal feed in Buwun Mas village is effective in overcoming the availability of animal feed in the dry season. Training in making animal feed helps farmers have the skills to mix their own animal feed to meet feed needs. Making fermented animal feed aims to utilize straw during the harvest season which is very abundant and it would be in vain if it is not processed into excellent and highly nutritious feed for livestock.